Modifying effects of vitamin D on associations between per- and polyfluoroalkyl substances exposure and risk of gestational diabetes mellitus: A prospective cohort study in Beijing, China - Feng Han; Ziwei Pei; Bing Lyu; Xin Zhang; Jian Zhang; Jiaying Liu (Environment International)
Epidemiology studies suggested that exposure to Per- and Polyfluoroalkyl Substances (PFAS) might elevate the incidence of Gestational Diabetes Mellitus (GDM), but no study considered the modifying roles of vitamin D, an important nutrient related to GDM development. Thus, this study evaluated the modifying effects of maternal vitamin D on correlations of PFAS exposure with GDM by conducting a cohort study in Beijing, China. We recruited 111 pregnant women who had either one or more high risk factors for GDM in Beijing, China, in 2022. Blood samples collected from pregnant women in 11–13 gestational weeks were analyzed to detect 19 PFAS and 25-hydroxy vitamin D. GDM was confirmed via the Oral Glucose Tolerance Test (OGTT). All subjects were classed as possessing sufficient, insufficient, or deficient vitamin D concentrations. Vitamin D deficiency status was observed to be a significant modifier for associations between GDM risk and PFAS exposure, as well as continuous glucose concentrations in an OGTT (interaction p-value < 0.05). For women with vitamin D deficiency, exposure to five long-chain perfluoroalkyl carboxylates significantly elevated the GDM risk (p < 0.05), and the overall estimated risk ratio for GDM associated with 1 ng/mL increases in PFAS ranged from 3.750 to 8.097. The results suggested that adequate supplementation of vitamin D during early pregnancy could prevent the elevated risk of GDM caused by PFAS exposure.